An exploration of protofacist tendencies in Robert Musil’s Die Verwirrungen des Zöglings Törless - Todd, Harrison (Kansas State University, 2011)
When Robert Musil saw his book, Die Verwirrungen des Zöglings Törless, published, he could not have seen the coming of fascist dictatorships. Despite this, two of Musil’s characters display characteristics that are hauntingly similar to characteristics common in the fascist Nazi movement in Germany and Austria, as well as protofascist groups such as the German Freikorps. By examining the characters of Beineberg and Reiting as well as their world in Die Verwirrungen des Zöglings Törless through the lens of thinkers such as Theodor Adorno and Klaus Theweleit, one can find many similarities between Musil’s characters and the fascists of the coming years. Although Beineberg and Reiting cannot take Adorno’s F-scale, which measures the authoritarian personality of individuals, there are many instances in which these characters’ actions and the F-scale overlap. One also discovers striking similarities between the tendencies of Musil’s characters and the fascistic tendencies of the Freikorps and other groups described in Klaus Theweleit’s book, Male Fantasies.
Keywords: Robert Musil; Die Verwirrungen des Zöglings Törless; Protofascism; Germanic Literature (0311)